Pelatihan Simulasi Kewirausahaan Bagi Anak Usia Dini di Kecamatan Ungaran Barat Kabupaten Semarang - Himmah Taulany; Nufitriani Kartika Dewi; Swantyka Ilham Prahesti (Universitas Mathla'ul Anwar Banten, 2018)
SIMULATION TRAINING OF ENTREPRENEURSHIP FOR EARLY CHILHOOD IN WEST UNGARAN SEMARANG. Community service activity at Kucica School, West Ungaran Sub-district, Semarang Regency is aimed to help Early Chilhood Education (PAUD) educators in Kucica and all Early Chilhood Education (PAUD) educators in general to organize entrepreneurship learning for early childhood. Early childhood characteristics that have not been able to think abstract require concrete learning and involve all the five senses. Community service activities are proposed after observing and analyzing existing problems in the field that is the need for learning innovation in entrepreneurship education in accordance with the characteristics of early childhood. The learning method that is done is the simulation of entrepreneurship of early childhood. This entrepreneurial simulation brings the real atmosphere of entrepreneurial activity with a microeconomic approach into the classroom but with a safe and comfortable atmosphere for young children to absorb entrepreneurial knowledge and experience. The simulation of early childhood entrepreneurship is intended so that the concepts and values ​​contained in entrepreneurship can be provided in early childhood. The ultimate goal of entrepreneurship education is the growth of the child entrepreneurial spirit from an early age in order to become a strong nation of children and able to compete in the next life arena.